The effectiveness of using tactical training techniques for tennis players 10–12 years old by using animated illustrations - Yevtyfiieva, I. I.; Yevtyfiiev, Andrii; Slepushkin, S. O.; Novomlynski, Ye. M. (Видавничий дім "Гельветика", 2021)
Purpose: substantiation of the effectiveness of using tactical training techniques by using animated illustrations in the training process of tennis players 10–12 years old. Materials and methods. The experiment involved 16 tennis players aged 10–12 years, each with 8 people. In the control group, the classes were conducted according to the traditional method, and in the experimental group, exercises with the use of animated illustrations and auxiliary specialized simulators for technical and tactical training of players were additionally introduced. Pedagogical observations were conducted in the process of training sessions. Psychophysiological testing was performed by using computer programs “Psychodiagnostics”, “Diagnostics” and the program S. Ermakova “Choice reaction”, as well as testing of technical and tactical readiness according to the international system of “International Tennis Number” (MTN). In the statistical analysis, a comparative analysis of the mean values and values for the Student’s t-criterion was carried out. Results. The principle of clarity of training is given and the interactive method of solving tactical tasks is used. It is shown that the applied method of training of tennis players has increased practically all indicators of testing of special physical and technical and tactical readiness, quality of execution of blows in draws. The developed method has a positive effect on the accuracy of strikes and the effectiveness of the completion of draws in matches. The developed method has a positive effect on the accuracy of shots and the effectiveness of the completion of draws in matches. Conclusions. Tactical combinations in tennis are very variable. The tactics of a tennis player depend on the style of play. However, it is difficult for athletes aged 10–12 to develop their style of play due to the psychological stress of competition. Thus, it is most effective to use in matches tactical combinations and actions studied in advance and brought to automatism. In our work the efficiency of application of a technique of tactical preparation of tennis players with the use of animated illustrations is proved. This technique has improved the quality and accuracy of strikes in a given area, as well as facilitated faster decision-making in game situations on the court. The developed technique is adequate to the solution of problems of training process on tactical preparation of tennis players of 10–12 years and can be recommended in wide practice of trainings of tennis players of age category till 10 years.

Мета: обґрунтування ефективності використання методики тактичної підготовки із застосуванням анімаційних ілюстрацій у тренувальному процесі тенісистів 10–12 років. Матеріали та методи. У дослідженні взяли участь 16 тенісистів віком 10–12 років, із них 8 тенісистів було обрано до складу експериментальної групи та 8 тенісистів увійшли до складу контрольної групи. У контрольній групі заняття проводилися за традиційною методикою, а в експериментальній групі додатково були введені вправи з використанням анімаційних ілюстрацій та допоміжні спеціалізовані тренажери з техніко-тактичної підготовки гравців. Педагогічні спостереження проводилися в процесі тренувань. Було проведено психофізіологічне тестування за допомогою комп’ютерних програм «Психодіагностика», «Діагност», програми С.С. Єрмакова «Реакція вибору», а також тестування техніко-тактичної підготовленості за всесвітньою системою «Міжнародного тенісного номеру» (MTN). У статистичному аналізі порівняно середні значення, значення критерію Стьюдента. Результати. Наведено принцип наочності навчання та використано інтерактивний метод вирішення тактичних завдань. Доведено, що метод навчання тенісистів, який застосовується, збільшив практично всі показники тестування спеціальної фізичної та техніко-тактичної підготовленості, якості виконання ударів у розіграшах. Розроблений метод позитивно впливає на точність ударів і результативність завершення розіграшів у матчах. Висновки. Тактичні комбінації у тенісі дуже варіативні. Тактика тенісиста залежить від стилю гри. Проте спортсменам віком 10–12 років складно виробити свій стиль гри через психологічну напругу на змаганнях. Таким чином, найефективнішим є використання у матчах заздалегідь вивчених та доведених до автоматизму тактичних комбінацій і дій. У нашій роботі розкрито ефективність застосування методики тактичної підготовки тенісистів із використанням анімаційних ілюстрацій. Ця методика дала змогу покращити якість і точність влучення ударів у визначену зону, а також сприяла більш швидкому ухваленню рішення в ігрових ситуаціях на корті. Розроблена методика адекватна розв’язанню завдань тренувального процесу з тактичної підготовки тенісистів 10–12 років і може бути рекомендована у широкій практиці тренувань тенісистів вікової категорії до 10 років.
Ефективність використання методики тактичної підготовки тенісистів 10–12 років із використанням анімаційних ілюстрацій
Keywords: tactics; training; animation; tennis; technology; тактика; підготовка; анімація; теніс; технології